Web-based Teaching in Particular Developing Counties, Experience at “Sulamani University” - Faraj, Kamaran Hama Ali A (International Journal of Computer Sciences and Engineering, 2025)
Throughout the progress of technology at Kurdistan Region Independent (KRI) Universities, it was investigated the influence of technological resources on teaching and learning at the KRI Universities. The all modifications of technological resources occurred from past up to now which created a new teaching and learning generation. Before year 2003 the traditional approach was applied in teaching and learning without any improvement due to the sanctions over Kurdistan Region by Ba'ath Regime. As a result of that, the universities at Kurdistan were isolated from the universal development of technology. Respectively, traditional teaching (TT) approach (or On-campus teaching) was more common at the University of Sulaimani as teachers had limited materials that they relied mainly on the suitable books for the course, face to face, and (whiteboard-and-marker) teaching. The new generation, namely electronic teaching (ET) (or Off-campus teaching) started after year 2003 because the University of Sulaimani did not go through all the stages of developing technology, therefore, most modern technology were brought to that university; for example network, computer and internet. However there is still a gap between TT and ET because of unavailability of electronic learning (e-learning) infrastructure or any e-learning (EL) center at that university so far. Despite that, the web base teaching (WBT) has not been functioned yet and that is turn out to be a gap between teachers, learner and technologies; in addition to that teachers and learners have been using technologies for the reason of teaching but they don’t have sufficient background about the fully e-teaching (ET). This paper discussed the function of modern technological devices components (computer, internet and networking) to teaching approach and the method that has been created here is a web base teaching (WBT), with multimedia devices by lecturing video synchronized with PowerPoint which contains of twenty five week- lectures loaded to specific domain name and students can retrieve whenever they want. Finally, this paper examines the results of In-class-Test between groups of ten students in Computer science Department which they will have test by both of the methods namely on & Off-campus-teaching.